Management of Academic Supervision to Improve Teacher Performance in the Teaching and Learning Process (PBM) At SDN 231 Sukaasih, Bandung City - Faiz Karim Fatkhulloh; Aan Puspita; Nani Suryani; Siti Hana Adlina Khairunnisa (al-Afkar, Journal For Islamic Studies, 2023)
This research is motivated by the situation in schools where there is still a learning process that is not in accordance with the plan, the teacher implements learning that is not in accordance with the objectives and all lesson plans, the teacher has not been able to make learning evaluations, the teacher teaches but students cannot be conditioned because they have not mastered methods, models and other preparations, so that there are still teacher performances that require guidance and direction to overcome the problems faced by teachers. In improving teacher performance in the teaching and learning process (PBM), school principals have an important role in pursuing all matters related to improving teacher performance in the teaching and learning process (PBM). This study discusses the management of academic supervision to improve teacher performance in the teaching and learning process (PBM) at SDN 231 Sukaasih Bandung City, where the target in the problem is how to plan, organize, implement and supervise/evaluate school principals to improve teacher performance in the teaching and learning process (PBM) at SDN 231 Sukaasih, Bandung City. Therefore the purpose of this study was to determine the planning, organizing, implementing and monitoring/evaluating of school principals to improve teacher performance in the teaching and learning process (PBM) at SDN 231 Sukaasih, Bandung City. The use of research methods in this research is qualitative which produces data in descriptive form. Data collection techniques in this study used observation, interviews and documentation studies. The results of this study emphasize more on meaning, because it uses qualitative research methods.